You look familiar … but what’s your name? Word learning in Singaporean older adults - Tan, Justina Yu Han (2019)
Although cognition and memory has been shown to decline with age, age-related disparities in performance may be mediated by group-appropriate learning methods. As such, understanding how words are learnt by older adults can be useful for developing language learning techniques for the aged population. A way to look at how novel words are learnt is through the use of face names, which have shown a familiarity advantage. This study compares word learning in bilingual Singaporean older adults and younger adults, investigating the role of referent familiarity in a name-learning task with pseudo words. A familiarization task was also introduced to facilitate recognition of an unknown face. Accuracy rates in 4 different conditions: (a) known-familiarized faces, (b) known-unfamiliarized faces, (c) unknown-familiarized faces, (d) unknown-unfamiliarized faces were compared and significant main effects of referent type, familiarization and age were found. A significant interaction was also found between age and familiarization. Interestingly, known faces were learnt better than unknown faces, but familiarized faces were learnt worse than unfamiliarized faces. However, while younger adults were negatively affected by the familiarization task, older adults seemed to benefit from the additional exposure. The findings suggest that age differences in word learning may require specialized learning methods to meet different needs.